0 - Prelim - Africa Development (Africa Development, 2020)
CODESRIA’s Meaning-making Research Initiative (MRI): A Note Godwin Murunga, Ato Kwamena Onoma & Ibrahim Oanda Ogachi ....... v Note sur les initiatives de recherche pour la construction du sens (MRI) Godwin Murunga, Ato Kwamena Onoma & Ibrahim Oanda Ogachi ..... xi University–Community Relations in Ghana: Traditional Authority as a Stakeholder Edmond A. Agyeman, Emmanuel M. J. Tamanja & Bernard B. B. Bingab..................1 Teacher Education, Common Purpose and the Forging of Multiple Publics In South Africa Nimi Hoffmann, Tarryn de Kock, Zahraa McDonald & Yusuf Sayed.................23 Entre la rue et l’internet : pratiques revendicatives et stratégies de mobilisation de Y’en a marre, du Balai citoyen, Filimbi et de la Lucha Mamadou Dimé, Pascal Kapagama, Zakaria Soré & Ibrahima Touré................. 53 The Discursive Dynamics of Action-Research and Zimbabwean San People’s Production of Audio-Visual Stories Nhamo A. Mhiripiri, Oswelled Ureke & Mercy M. Mubayiwa......................73 La scène musicale populaire kinoise à l’épreuve du genre et de l’androcentrisme Léon Tsambu.............................................................................................. ......................................................... 107 Impact Pathways of Weather Information for Smallholder Farmers: A Qualitative ex ante Analysis Rosaine N. Yegbemey, Aline M. Aloukoutou and Ghislain B. D. Aihounton...................... 133 Locked-in Metaphorically: The War on Hawking in Nairobi’s CBD and the Cat-and-Mouse Game ani, Sammy G. Gachigua, George M. Kariuki 157 .......................